Case Report: A Nasopharyngeal Cancer Patient Got COVID-19 During Radiochemotherapy in Wuhan - Qiu, Weiming; Yi, Fengtao; Ren, Xingfeng; Li, Zhaoxia; Wang, Deqiang; Wang, Ning (Frontiers in Oncology, 2020)
The coronavirus disease (COVID-19) infection caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has spread worldwide. Reports of COVID-19 among cancer patients are limited and most studies focus mainly on its epidemiological and clinical features. In this study, we report the case of a nasopharyngeal cancer patient from Wuhan who contracted COVID-19 during radiochemotherapy and has since recovered from the infection. We hope that this report will provide valuable insights into the treatment of SARS-CoV-2-infected cancer patients through an account of our experience.